Spectral techniques in digital logic - Chang, Chip Hong. (2010)
In digital logic design, spectral techniques have been used for more than 30 years. The bottleneck of spectral techniques has been the exponential resources required to calculate and store the spectral coefficients. Recently, spectral techniques coupled with efficient data structures like Cube Calculus and Binary Decision Diagram have evolved to address this issue. In this thesis, relations between spectral data and these reduced representations are investigated in a different perspective. The goal is to achieve an unified procedure for the mutual conversions between spectra and reduced representations for various transforms, with or without a recursive structure, for both completely and incompletely specified logic functions.